Analisis Peran Keluarga Terhadap Keselamatan Pasien Dalam Upaya Pencegahan Resiko Jatuh Pada Anak Di Rsud Al-Ihsan Provinsi Jawa Barat - Zulviani, Salsabila; Ariyani, Nurul Dwi (Barongko: Jurnal Ilmu Kesehatan, 2024)
This study aims to determine family knowledge of patient safety in efforts to prevent the risk of falls in children at Al-Ihsan Regional Hospital. Many factors influence the incidence of patient falls, especially the role of the family in looking after the patient in the inpatient room which is very important in preventing the high risk of patient falls. The research method used is a qualitative method with data collection techniques in the form of an online questionnaire (Google form) which is distributed in the form of a link to be answered with a total of 30 respondents. From the results of this study, it can be concluded that only 23 parents knew that their child was at risk of falling, while 7 other people said they did not know that the child being cared for was at risk of falling. The advice given to overcome this problem is to communicate between health officials and parents to provide optimal care for children, and solutions to prevent unwanted events by providing health knowledge.